Makna Avatar Couple pada Pengguna Media Sosial Discord - Risman Maulana; Anne Maryani (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Couple avatars have become one of the things that we encounter quite often, especially when we are browsing via the internet. It's not uncommon for us to find two-dimensional photographs or avatars that show a pair of lovers. The purpose of conducting this research is to find out how the motives, experiences, and also the meaning of the avatar couple users use the avatar couple. Data collection techniques in this study used in-depth interviews and observation. Based on the results of the study, it was found that the motives of discord social media users in using the avatar couple were seeking attention, and providing a sense of security, being invited by a partner, being forced, and because they saw other people. Abstrak. Avatar couple telah menjadi salah satu hal yang cukup sering kita temui, terkhusus ketika kita berjelajah lewat internet. Tidak jarang kita temui foto-foto atau avatar dua dimensi yang menunjukkan layaknya sepasang kekasih. Tujuan dari dilakukannya penelitian ini adalah untuk mengetahui bagaimana motif, pengalaman, dan juga makna dari para pengguna avatar couple dalam menggunakan avatar couple. Teknik pengumpulan data dalam penelitian ini menggunakan wawancara mendalam, dan observasi. Berdasarkan hasil penelitian, ditemukan bahwa motif dari pengguna media sosial discord dalam menggunakan avatar couple yaitu mencari perhatian, dan memberikan rasa aman, diajak oleh pasangan, terpaksa, dan karena melihat orang lain.